Structure–property relationship of recycled carbon fibres revealed by pyrolysis recycling process - Jiang, Guozhan; Pickering, Stephen J. (Springer, 2016)
The structure-property relationship for recycled carbon fibres is investigated by characterisation of the structure changes induced by the pyrolysis recycling process. Two important factors influencing the properties of recycled carbon fibres are identified for various recycling processes: oxidative effect and thermal effect. The oxidative effect results in surface defects, and the surface defects causes a reduction in tensile strength and lateral crystallite size. The thermal effect of the recycling process results in an expansion in the distance between graphite layers and a decrease in surface oxygen concentration, which would lead to a drop in interfacial shear strength with epoxy resins. The tensile strength of recycled carbon fibres has a strong correlation with the intensity ratio of the D and G bands of the Raman spectra (ID/IG). With an increase in ID/IG, the tensile strength of recycled carbon fibre decreases linearly.